2012
DOI: 10.1002/mabi.201100422
|View full text |Cite
|
Sign up to set email alerts
|

Injectable in situ Physically and Chemically Crosslinkable Gellan Hydrogel

Abstract: An injectable, in situ physically and chemically crosslinkable gellan hydrogel is synthesized via gellan thiolation. The thiolation does not alter the gellan’s unique 3-D conformation, but leads to a lower phase transition temperature under physiological conditions and stable chemical crosslinking. The synthesis and hydrogels are characterized by 1H NMR, FT-IR, CD, or rheology measurements. The injectability and the tissue culture cell viability is also tested. The thiolated gellan hydrogel exhibits merits, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…[ 59,60 ] A radical source, commonly azobisisobutylonitrile, is then added along with thioacetate, and the resulting thioester is deprotected with sodium hydroxide to reveal the thiol group. Alternately, functionalized thiol compounds such as thioglycolic acid, [ 61 ] cysteine, [ 62 ] and N -acetyl-L-cysteine [ 63,64 ] can be conjugated to complementary amine or carboxylic-acid-functionalized polymer backbones via carbodiimide coupling, although this method can suffer from potential cross-reactivity of the thiol with the electrophile in the thiol-containing compound to generate poorly defi ned polymers. Disulfi de-containing compounds can also be grafted to polymers and/or used as cross-linkers to create hydrogels and then reduced to expose free thiols.…”
Section: Tissue Interactionsmentioning
confidence: 99%
“…[ 59,60 ] A radical source, commonly azobisisobutylonitrile, is then added along with thioacetate, and the resulting thioester is deprotected with sodium hydroxide to reveal the thiol group. Alternately, functionalized thiol compounds such as thioglycolic acid, [ 61 ] cysteine, [ 62 ] and N -acetyl-L-cysteine [ 63,64 ] can be conjugated to complementary amine or carboxylic-acid-functionalized polymer backbones via carbodiimide coupling, although this method can suffer from potential cross-reactivity of the thiol with the electrophile in the thiol-containing compound to generate poorly defi ned polymers. Disulfi de-containing compounds can also be grafted to polymers and/or used as cross-linkers to create hydrogels and then reduced to expose free thiols.…”
Section: Tissue Interactionsmentioning
confidence: 99%
“…In addition to these gelation properties, GG's excellent optical clarity could prove advantageous in analysis of encapsulated cells 7 . It has been 55 shown that GG scaffolds can be made porous using straightforward fabrication methods 52 . Furthermore, GG appears not to inhibit polymerase chain reaction (PCR) analysis 53 and is suitable as an injectable material [54][55][56] .…”
Section: Why Consider Gellan Gum?mentioning
confidence: 99%
“…It has been 55 shown that GG scaffolds can be made porous using straightforward fabrication methods 52 . Furthermore, GG appears not to inhibit polymerase chain reaction (PCR) analysis 53 and is suitable as an injectable material [54][55][56] . A further attractive characteristic of GG for TE are the 60 mechanical similarity to the elastic moduli of common tissue.…”
Section: Why Consider Gellan Gum?mentioning
confidence: 99%
See 1 more Smart Citation
“…They essentially provide a scaffold around which tissues can be engineered with an architecture that is reflective of the native tissue being targeted. This ability is essential to successfully applying tissue engineering as a medical method [7].…”
Section: Introductionmentioning
confidence: 99%